The Effect of Pharmacist Education Using the Brief Counseling Method on Improving Medication Adherence in Hypertensive Patients - Cut Alfaini Rahmah Fauzana; Khairunnisa Khairunnisa; Azizah Nasution (Jurnal FARMASIMED (JFM), 2026)
Background: The main problem in controlling hypertension is patients' low knowledge about the disease, complications, and the importance of adherence to long-term therapy. Objective: This study analyzes the effect of pharmacist education using brief counseling in improving the adherence of hypertensive patients. Methods: Quasi-experimental pretest and posttest with control group. The intervention took the form of brief counseling with leaflets using the 5A technique on hypertensive patients who met the inclusion criteria during July–October 2025. Compliance data were analyzed using the Wilcoxon test to determine the differences in the results of each group and the Mann-Whitney test to determine the differences between groups before and after the intervention. A total of 190 patients were followed up for one month, consisting of 96 control groups and 94 intervention groups. The intervention group was followed up in months 1 and 2 after the intervention. Results: The characteristics of respondents were dominated by women (86.8%), aged ≥65 years (36.8%), unemployed (62.1%), and high school education (45.2%). The results showed that in the intervention group there was an increase in compliance from 14.77 ± 3.817 to 24.67 ± 0.847 (p < 0.001). Meanwhile, in the control group, compliance increased from 15.31 ± 4.107 to 15.65 ± 4.063 (p = 0.083). Although compliance decreased in the first (24.64 ± 0.828) and second (24.61 ± 0.779) months of follow-up, there was no statistically significant difference from the posttest results. Conclusion: Education using brief counseling method can increase adhererence hypertension patients and effective in maintaining adherence for to two months.